2021
DOI: 10.1134/s1061830921020042
|View full text |Cite
|
Sign up to set email alerts
|

Impact Damage Detection in Laminate and Honeycomb CFRPs using Lamb Wave Ultrasonic Sensing

Abstract: The paper presents the results on application of Lamb waves based technique for impact damage detection and severity identification. The PZT network operates in the round-robin mode changing the actuator and sensor roles of the transducers in order to detect the response of the system in the presence of damage. The monitoring is performed via the analysis of three parameters: change of the amplitude (dA), change of the energy (dP) and cross-correlation (NCC) of the signals in baseline and damaged state. Testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
(39 reference statements)
0
3
0
1
Order By: Relevance
“…Since these delaminations are typically at least within the size range of the considered wavelength, only linear wave propagation is analyzed here. The influence of delaminations and impact damage on linear wave propagation has been intensely investigated over the years [ 5 , 6 , 15 , 18 , 19 , 20 , 21 ]. It is shown that the scattered and converted mode amplitudes depend on the fiber orientation, the delamination size as well as the relative position along the laminate’s height [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since these delaminations are typically at least within the size range of the considered wavelength, only linear wave propagation is analyzed here. The influence of delaminations and impact damage on linear wave propagation has been intensely investigated over the years [ 5 , 6 , 15 , 18 , 19 , 20 , 21 ]. It is shown that the scattered and converted mode amplitudes depend on the fiber orientation, the delamination size as well as the relative position along the laminate’s height [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they then studied the feasibility of a piezoelectric diaphragm instead of piezoelectric ceramic and compared the effect of temperature variation on both sensors [ 3 ]. The variations in the amplitude, energy and cross-correlation of signals in health and damage states was researched by Burkov et al [ 4 ]. Furthermore, the severity of the damage was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Связанной с ней задачей является неразрушающая диагностика фазового состава и повреж денности образцов и элементов структур различного назначения из композитных материалов, что крайне важно в контексте создания цифровых двойников конечных изделий. Для решения этих проблем развиваются различные неразрушающие методы, в том числе основанные на анализе скоростей и дисперсии упругих волн [1][2][3][4][5][6]. Развитие таких методов базируется на построении математического формализма, позволяющего связывать интегральные упругие характеристики композитного материала, MECHANICS OF COMPOSITE MATERIALS.-2022.-Vol.…”
Section: Introductionunclassified